Indigenous traditions and the impact of war: An analysis of N. Scott Momaday’s House Made of Dawn - Nazki, Sameeul Haq (Goodwood Publishing, 2024)
Purpose: This study analyzes indigenous traditions and the impact of war on N. Scott Momaday’s novel House Made of Dawn. This study aims to understand how the narrative portrays the struggles of Native American identity and cultural survival in the post-World War II era. Research methodology: A qualitative literary analysis approach was employed, focusing on thematic analysis, character study, and the cultural context. The analysis examined primary and secondary sources, such as literary criticism and historical accounts, to provide a comprehensive understanding of the novel’s themes. Results: The analysis revealed that the novel intricately weaves indigenous traditions with traumatic experiences of war. The protagonist, Abel, embodies the conflict between Native American heritage and the alienation caused by modern society and war. The novel depicts the resilience of indigenous culture through rituals, storytelling, and community support, highlighting the healing process of individuals and communities. Limitations: This study’s narrow focus on a single novel may not fully represent the broader spectrum of Native American literature or experiences. Additionally, reliance on existing literary criticism may introduce bias, based on the interpretations of other scholars. Contribution: This paper enhances the understanding of how indigenous traditions and the impact of war are portrayed in the Native American literature. This underscores the importance of cultural preservation and the role of literature in addressing historical and contemporary issues faced by indigenous communities. This study also offers insights into the healing power of cultural practices and community solidarity in the face of adversity.